Fast chromatographic determination of polycyclic aromatic hydrocarbons in aerosol samples from sugar cane burning - Godoi, AFL; Ravindra, K.; Godoi, RHM; Andrade, S. J.; Santiago-Silva, M.; Van Vaeck, L.; Van Grieken, R. (Elsevier B.V., 2004)
Sugar cane burning in Brazil causes remarkable amounts of organic compounds to be emitted amongst which the polycyclic aromatic hydrocarbons (PAHs) represent serious health hazards. Therefore, 24-h aerosol samples (< 10 mum aerodynamic diameter) were collected in Araraquara city (São Paulo state) during the harvest season using a Hi-Vol sampler. PAHs were recovered using an Accelerated Solvent Extractor and analyzed by low-pressure gas chromatography-ion trap mass spectrometry (LP-GC-IT-MS). The fully automated extraction process was performed in less than 25 min with a solvent consumption of approximately 20 ml. The use of a deactivated 0.6 m x 0. 10 mm i.d. restrictor coupled to a 10 m wide-bore analytical column allowed most of the 16 PAHs in EPA's priority list to be identified and quantified in only 13 min. Concentrations of PAHs in Nraraquara aerosols ranged between 0.5 and 8.6 ng m(-3). (C) 2003 Elsevier B.V. All rights reserved.
Keywords: aerosols; air analysis; environmental analysis; polynuclear aromatic hydrocarbons